Persepsi Distance Learning Ditinjau Dari Motivasi Belajar Mahasiswa - Hikayat, Chairil; Latif, Ikhsan Abdul; Jana, Padrul (Universitas Pekalongan, 2025)
This research is motivated by the emergence of the transition to an increasingly massive distance learning process in Indonesia since the emergence of COVID-19 in Indonesia. The study aims to look at student perceptions of the distance learning process on student learning motivation. The design used in the research uses a type of quantitative research with a descriptive approach, the data collection process uses a questionnaire taken through Google Forms on active students of the ITBMP actuarial and digital business study program using descriptive data analysis. The data obtained is processed using the Likert method. The results of the study found from 11 statements that contained learning motivation indicators show that learning motivation is related to the process and methods in the learning process, the results of the questionnaire from six indicators obtained 16% got a positive response while 84% got a negative response. From the results of the research conducted by researchers, the results reveal that students have a low level of motivation towards distance learning.